Parenting trajectories in Singapore: exploring longitudinal profiles and their implications for child problems - Cheong, Vanessa Wan Xuan (Nanyang Technological University, 2024)
Parenting is a multifaceted and dynamic process, where it is influenced by one’s culture, and is continuously evolving to meet children’s individual and developmental needs. Therefore, classifying parenting into predefined categories falls short in capturing its full complexity, warranting it to be studied from a holistic and longitudinal perspective. Using a longitudinal and person-centred approach, the present study explored harsh and supportive parenting simultaneously, established profiles that reflect the trajectories of maternal parenting practices from early to middle childhood, and investigated the implications of these profiles on later child internalising and externalising problems. The sample consisted of 593 mother-child dyads recruited as part of the Growing Up in Singapore Towards healthy Outcomes (GUSTO) birth cohort study. Mothers reported on their use of harsh and supportive parenting when the child was aged 4.5, 8.5 and 10.5 years old, while children reported on their internalising and externalising problems when they were 12 years old. Variations in the initial levels and changes in maternal use of harsh and supportive parenting were evident. Further analyses revealed that Singaporean mothers could be classified into three parenting trajectory profiles: Reserved, Regimental and Nurturing. Children of mothers who adopted a Regimental parenting profile reported greater externalising problems, however, this association became non-significant after accounting for early childhood externalising problems. These parenting trajectory profiles were not significantly associated with later child internalising problems. The findings suggested that mothers in Singapore employ harsh and supportive parenting concurrently, with variations observed as children transition from early to middle childhood.